The Association of Body Composition and Musculoskeletal Characteristics with Police Recruit Performance: A Cross-Sectional Study - Vanessa R. Sutton; Myles C. Murphy; Callum J. McCaskie; Paola T. Chivers; Nicolas H. Hart; Jodie L. Cochrane Wilkie; Garth Allen; Jack Dalla Via (Journal of Functional Morphology and Kinesiology)
Objective: Exploring how body composition and musculoskeletal characteristics relate to physical performance may provide insights for optimising training outcomes. We explored if body composition and musculoskeletal characteristics were associated with tactical and cardiorespiratory performance. Methods: A cross-sectional study of police recruits within the Western Australia Police Force was performed. Total and regional body composition was assessed using Dual-energy X-ray Absorptiometry, with the tibial morphology and mid-thigh muscle cross-sectional area assessed using peripheral Quantitative Computed Tomography. Tactical performance was measured with a Physical Performance Evaluation, and cardiorespiratory fitness assessed using the Beep Test. Variables that were significant in univariate regressions progressed to generalised linear models, assessing relationships between measures and performance outcomes. Results: Twenty-seven recruits aged 21–51 years (40.7% female) participated. Better tactical performance was associated with lower body fat percentage (p < 0.001), lower body mass index (p < 0.001), higher appendicular muscle mass (p = 0.005), and a lower proximal (66%) tibia polar cross-section moment of inertia (p = 0.007). Better cardiorespiratory fitness was associated with lower body fat percentage (p = 0.004), higher appendicular lean mass (p = 0.006), a lower proximal (66%) tibia polar cross-section moment of inertia (p = 0.005), and a higher mid-thigh muscle cross-sectional area (p < 0.001). Conclusions: Various body composition and musculoskeletal characteristics are associated with tactical performance and cardiorespiratory fitness in WA police recruits. Lower body fat percentage and higher appendicular muscle mass were associated with both better cardiorespiratory fitness and tactical performance, highlighting the potential relevance of these characteristics in preparing police recruits for operational duties.